Functional Properties of Dunaliella salina and Its Positive Effect on Probiotics - Hyrslova, Ivana; Krausova, Gabriela; Mrvikova, Iva; Stankova, Barbora; Branyik, Tomas; Malinska, Hana; Huttl, Martina; Kana, Antonin; Doskocil, Ivo (Marine drugs, 2022)
The unicellular green microalga Dunaliella is a potential source of a wide range of nutritionally important compounds applicable to the food industry. The aim of this study was to assess the effect of Dunaliella salina dried biomass on the growth and adherence of 10 strains of Lactobacillus, Lacticaseibacillus, and Bifidobacterium. The immunomodulatory, antioxidant, and cytotoxic effects of D. salina on human peripheral mononuclear cells and simulated intestinal epithelial cell lines Caco-2 and HT-29 were evaluated. Furthermore, the hypocholesterolemic effects of the microalgae on lipid metabolism in rats fed a high-fat diet were analyzed. The addition of D. salina biomass had a positive effect on the growth of nine out of 10 probiotics and promoted the adherence of three bifidobacteria strains to human cell lines. The antioxidant and immunomodulatory properties of D. salina were concentration-dependent. The inflammatory cytokines (TNF-α and IL-6) were significantly increased following Dunaliella stimulation at the lowest concentration (0.5% w/v). Eight week supplementation of D. salina to the diet of hypercholesteromic rats significantly decreased the serum concentrations of LDL-C, VLDL, IDL-B, and IDL-C. D. salina is not cytotoxic in intestinal cell models; it promotes adherence of selected bifidobacteria, it affords immunomodulatory and antioxidant effects, and its addition to diets may help decrease atherosclerosis risk factors.
Keywords: Caco-2 Cells; Rats; mikrořasy; Antioxidants; Caco-2 buňky; Chlorophyceae; adherence; Dunaliella salina; krysa rodu Rattus; algae; antioxidancia; cytokine; zvířata; Humans; prebiotic; Biomass; Microalgae; lidé; biomasa; Animals